Correlación entre el índice leucoglucémico y escala de NIHSS en pacientes con Ictus isquémico agudo - Flores Navarro, Henry (2021)
Cerebrovascular disease (CVD) is a clinical syndrome of sudden onset, due to the sudden focal and vascular interruption of brain functions in a period greater than 24 hours and evidenced by neuroimaging; Together with the measurement of the leukoglycemic index upon admission of the patient due to emergency, it has been related to a greater in-hospital complication, failed thrombolysis, and death. The objective measurement of the level of functional dependence after CVD determines the functional prognosis of the patient, the most used scale is NIHSS, which has become the most practical tool to assess the initial neurological state of the patient